Impact of Order Restrictions on Hemoglobin A1c Requests at Primary Health Care Centers in Riyadh, Saudi Arabia - Alakeely M; Masud N; Bin Saleh F; Alghassab R; AlFagih N; Alkathiri MA; Albakri S (Risk Management and Healthcare Policy)
Maha Alakeely,1,2 Nazish Masud,3 Fatemah Bin Saleh,1,2 Razan Alghassab,4 Nouf AlFagih,4 Moath Abdulmohsen Alkathiri,1,2 Sarrah Albakri1,2 1Department of Family Medicine, King Abdulaziz Medical City, Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia; 2King Abdullah International Medical Research Centre, Riyadh, Saudi Arabia; 3Department of Biostatistics Epidemiology and Environmental Health Sciences, Jiann-Ping HSU College of Public Health, Georgia Southern University, Statesboro, Georgia, USA; 4Lean Business Services, Riyadh, Saudi ArabiaCorrespondence: Maha Alakeely, Department of Family Medicine, King Abdulaziz Medical City, Ministry of National Guard Health Affairs, P.O. Box 123194, Riyadh, 11741, Saudi Arabia, Email Mahaakeely@gmail.comPurpose: The aim of the study was to assess the effect of policy intervention on the physician ordering of HbA1c for the patients seen at the primary health care center in Riyadh, Saudi Arabia.Methods: The study included patients over the age of 18 for whom HbA1c tests were ordered before and after the policy restrictions were implemented at the three main Primary Health Care Centers under the Ministry of National Guard Health Affairs (MNGHA) in Riyadh, between October 2020 and August 2023. Several data management steps and restrictions were carried out to identify the patients seen before and after the intervention and controlled for the confounders. The outcome variable was inappropriate testing, and early testing was defined based on standard cutoffs of HbA1c, diabetic control, and patient history. The logistic regression analysis was used to identify predictors for early testing.Results: Among 16,290 participants, the mean age was 50 ± 16 years, with a predominance of females (66.5%). Approximately 22.3% of participants were diabetic, and the mean HbA1c level was 6.2 ± 1.55%. About 89.6% of tests were deemed inappropriate based on criteria for glycemic control, diabetic status, and duration of testing. Policy restrictions led to a 70.3% reduction in the odds of early testing (OR = 0.297, 95% CI: 0.246– 0.358, p < 0.001). Each unit increase in HbA1c decreased the odds of early testing by 1.517 (OR = 0.219, 95% CI: 0.193– 0.249, p < 0.001). Additionally, younger participants were more likely to undergo early testing, with odds decreasing by 3% for each additional year of age (OR = 0.970, 95% CI: 0.966– 0.974, p < 0.001).Conclusion: We conclude that policy restriction alone might not be effective in reducing the burden of early testing. The early testing tendency was less in the post-intervention period. However, early testing was a common practice in both pre- and post-intervention phases. As physicians are the ones ordering the tests, deeper insight is needed from the physician’s perspective.Keywords: HbA1c, policy, Saudi Arabia, laboratory-testing, physicians